The Common Bean V Gene Encodes Flavonoid 3′5′ Hydroxylase: A Major Mutational Target for Flavonoid Diversity in Angiosperms - McClean, Phillip E.; Lee, Rian; Howe, Kevin; Osborne, Caroline; Grimwood, Jane; Levy, Shawn; Haugrud, Amanda Peters; Plott, Chris; Robinson, Melanie; Skiba, Ryan M.; Tanha, Tabassum; Zamani, Mariam; et al. (Frontiers in Plant Science, 2022)
The classic V (violet, purple) gene of common bean (Phaseolus vulgaris) functions in a complex genetic network that controls seed coat and flower color and flavonoid content. V was cloned to understand its role in the network and the evolution of its orthologs in the Viridiplantae. V mapped genetically to a narrow interval on chromosome Pv06. A candidate gene was selected based on flavonoid analysis and confirmed by recombinational mapping. Protein and domain modeling determined V encodes flavonoid 3′5′ hydroxylase (F3′5′H), a P450 enzyme required for the expression of dihydromyricetin-derived flavonoids in the flavonoid pathway. Eight recessive haplotypes, defined by mutations of key functional domains required for P450 activities, evolved independently in the two bean gene pools from a common ancestral gene. V homologs were identified in Viridiplantae orders by functional domain searches. A phylogenetic analysis determined F3′5′H first appeared in the Streptophyta and is present in only 41% of Angiosperm reference genomes. The evolutionarily related flavonoid pathway gene flavonoid 3′ hydroxylase (F3′H) is found nearly universally in all Angiosperms. F3′H may be conserved because of its role in abiotic stress, while F3′5′H evolved as a major target gene for the evolution of flower and seed coat color in plants.